DESIGN, CONSTRUCTION AND EVALUATION OF A THERMAL CONDUCTIVITY METER BASED ON ASTM E1225 STANDARD - Manetti, L. L.; Dias Jr, I.; Kiyomura, I. S.; Cavalcanti, R. C.; Pagliosa, F. B. (Revista de Engenharia Térmica, 2016)
The focus of this work is the design, construction and evaluation of a thermal conductivity meter apparatus based on ASTM E- 1225 standard. The thermal conductivity is a heat-transport propriety and with the development of new materials the determination of thermophysical properties for its correct use becomes necessary. The apparatus was projected in CAD software and the material selection was done following the standard recommendations. For the meter bars were used 304 stainless steel, since its thermal conductivity is known. The heater was made with an aluminum cylinder block and a cartridge electric resistance. The cooling system was assembled using a Peltier thermoelectric plate and a fin heat sink equipped with a fan. Lastly, a steel pipe was used for building the guard cylinder. In order to evaluate the apparatus, the first specimen tested was the 304 stainless steel, the same material as the meter bars. The result of thermal conductivity showed an error of 6% relative to the value found in literature. However, in this test the temperature of isothermal guard cylinder was lower than the temperature required by the standard. Thus, the future goals will be the development of a temperature control for the guard cylinder and realization of more tests with different materials.